2011
DOI: 10.1155/2011/284795
|View full text |Cite
|
Sign up to set email alerts
|

Tylosema esculentum (Marama) Tuber and Bean Extracts Are Strong Antiviral Agents against Rotavirus Infection

Abstract: Tylosema esculentum (marama) beans and tubers are used as food, and traditional medicine against diarrhoea in Southern Africa. Rotaviruses (RVs) are a major cause of diarrhoea among infants, young children, immunocompromised people, and domesticated animals. Our work is first to determine anti-RV activity of marama bean and tuber ethanol and water extracts; in this case on intestinal enterocyte cells of human infant (H4), adult pig (CLAB) and adult bovine (CIEB) origin. Marama cotyledon ethanolic extract (MCE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Several recent studies demonstrate that plant extracts are deeply explored for their antiviral potential against HRoV [914, 27–29]. …”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies demonstrate that plant extracts are deeply explored for their antiviral potential against HRoV [914, 27–29]. …”
Section: Discussionmentioning
confidence: 99%
“…Seeds are also used to produce milk, oil, and flour, while the tubers, which can grow up to 200 kg in size, are used as sources of carbohydrate, protein, and water [168]. Extracts from this species are commonly used to treat inflammatory disorders, viruses, and skin diseases [169,170].…”
Section: Marama Beanmentioning
confidence: 99%
“…Previous studies investigated the antiviral activity of several plant extracts against rotavirus. Chingwaru et al (2011) reported high in vitro inhibition of rotavirus by Tylosema esculentum (marama) which are used as food and as a traditional medicine against diarrhea in Southern Africa. Also, fourteen Brazilian medicinal plants traditionally used for the treatment of diarrhea were investigated for their activity against rotavirus.…”
Section: Introductionmentioning
confidence: 99%